问题 解答题
7
13
×
3
4
+
3
4
×
6
13
         
3
7
÷
7
11
+
4
7
÷
7
11
12
7
÷(
2
3
-
1
4
5
9
+
5
9
÷
5
3
16
5
×
1
2
÷
2
5
        
⑥36×(
7
9
+
5
6
)÷
29
5
答案

7
13
×
3
4
+
3
4
×
6
13
 

=

3
4
×(
7
13
+
6
13

=

3
4
×1

=

3
4
;       

5
9
+
5
9
÷
5
3

=

5
9
+
5
9
×
3
5

=

5
9
×(1+
3
5

=

5
9
×
8
5

=

8
9
   
3
7
÷
7
11
+
4
7
÷
7
11

=

3
7
×
11
7
+
4
7
×
11
7

=

11
7
×(
3
7
+
4
7

=

11
7
×1

=1

4
7

16
5
×
1
2
÷
2
5
 

=

16
2
×
1
2
×
5
2

=10;

12
7
÷(
2
3
-
1
4

=

12
7
÷(
8
12
-
3
12

=

12
7
÷
5
12

=

12
7
×
12
5

=

144
35

=4

4
35

⑥36×(

7
9
+
5
6
)÷
29
5

=36×(

14
18
+
15
18
)×
5
29

=36×

29
18
×
5
29

=10.

单项选择题 A1/A2型题
单项选择题